Increased antioxidant quality versus lower quantity of high density lipoprotein in benign prostatic hyperplasia - Aydin Ozgur; Yasar Ellidag Hamit; Eren Esin; Ay Nurullah; Yalçinkaya Soner; Yilmaz Necat (Journal of Medical Biochemistry, 2015)
Background: Oxidative stress may be involved in the pathogenesis of every human disease. To understand its possible role in benign prostatic hyperplasia (BPH), we measured the overall oxidative status of patients with BPH and the serum activity of the high density lipoprotein (HDL)-related antioxidant enzymes paraoxonase 1 (PON1) and arylesterase (ARE). Methods: Fifty-six urology outpatient clinic patients with BPH (mean age 64± 8.6 years) were prospectively included in the study. Forty volunteer healthy controls from the laboratory staff (mean age 62±10 years) were enrolled for comparison. Serum total antioxidant status (TAS), total oxidant status (TOS), PON1, ARE, and HDL levels were measured by commercially available, ready-to-use kits. Results: Serum TAS and HDL levels were significantly lower in the BPH group than in the control group (P=0.004 and P=0.02, respectively). No significant between-group differences were observed for TOS levels or PON1 and ARE enzyme activities (P=0.30, P=0.89, and P=0.74, respectively). In the BPH group, the calculated parameters PON1/HDL and ARE/HDL were significantly higher (P=0.02 and P=0.04, respectively). Conclusions: Our findings agree with the previous reports of impaired oxidant/antioxidant balance in BPH patients. The activities of HDL-related enzymes between groups with significantly different HDL levels may be deceptive; adjusted values may help to reach more accurate conclusions.